Investigating the causal relationship between renewable energy consumption and life expectancy in Turkey: A Toda-Yamamoto causality test - Ekrem Yılmaz; Fatma Şensoy (International Econometric Review (IER), 2023)
This study examines the causal relationship between renewable energy consumption and life expectancy in Turkiye using the Toda-Yamamoto causality test. By analyzing data from 1990 to 2019, the study explores the relationship between these variables. The results of the Toda-Yamamoto causality test indicate that there is no Granger causality relationship from renewable energy consumption to life expectancy, indicating that renewable energy consumption does not have a significant impact on life expectancy in Turkiye. However, the study found a Granger causality relationship from life expectancy to renewable energy consumption, suggesting that improving life expectancy could lead to an increase in renewable energy consumption in Turkiye. This study is significant as it provides insights into the relationship between renewable energy consumption and life expectancy in Turkiye. The results highlight the importance of considering factors other than renewable energy consumption when examining public health outcomes. The study's findings can inform policymakers in developing energy policies that prioritize public health outcomes and promote sustainable energy practices.
Keywords: Q42; I12; O44; Q56; C22; 330; Life expectancy; Renewable energy consumption; Toda-Yamamoto causality test; Sustainable energy policies; public health